Analysis of The Merger Effects - The Case of United Airlines and Continental Airlines - Stankevich, Maksim; Sieber, Patrik, 1977-; Srivastava, Mohit; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
The aim of the current master’s thesis is to estimate the merger effects of the airline companies United and Continental. Additionally, it was set to identify the motives of the merger in relation to the airline industry. After the review of available theoretical literature of M&A the main drivers and specifics of M&A in the airline industry were identified. The financial ratio analysis was conducted based on the statistical sources and airlines annual reports. Moreover, the counterfactual analysis of the transaction helped to purify and estimate the effects of the merger. The motives and effects were identified and there were provided possible reasons for the achieved results.
Vedoucí práce: Patrik Sieber
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses